An Increase in Estimation Accuracy Position Determination of Inertial Measurement Units - Beran, Ladislav; Chmelař, Pavel; Rejfek, Luboš (E D P SCIENCES, 2016)
This paper deals with an increase in measurement accuracy of the Inertial Measurement Units (IMU). In the Inertial Navigation Systems (INS) a fusion of gyroscopes, accelerometers and in some cases magnetometers are typically used. The typical problem of cheap IMU is non-stationary offset and high level of noise. The next problem of IMU is a problem with a bumpy floor. For this case it is necessary to a have high quality chassis to eliminate additional noise. Also, it is possible to eliminate this noise by using some algorithm, but results are still poor. These properties lead to the inaccurate position estimation in the integration process. Even a small offset error leads to a big mistake in position determination and grows quickly with a time. This research is focused on the elimination of these poor properties and increase of accuracy of position estimation using Kalman Filtration.
Zvýšení přesnosti určení polohy inerciálních měřicích jednotek
Keywords: Increase; Estimation; Accuracy; Position; Determination; Inertial; Measurement; Units; Inerciální měřicí jednotka; Inerciální navigace; Měření přesnosti; Určení polohy